Selective decontamination of the digestive tract in upper gastrointestinal surgery: systematic review with meta‐analysis of randomized clinical trials. Issue 6 (4th August 2020) - Scheufele, F.; Schirren, R.; Friess, H.; Reim, D.
Abstract : Background: Infectious complications are common after gastrointestinal surgery. Selective decontamination of the digestive tract (SDD) might reduce their incidence. SDD is used widely in colorectal resections, but its role in upper gastrointestinal resection is less clear. The aim of this study was to investigate the impact of SDD on postoperative outcome in upper gastrointestinal surgery. Methods: Studies investigating SDD in upper gastrointestinal surgery were included after search of medical databases (PubMed, Ovid, Cochrane Library and Google Scholar). Results were analysed according to predefined criteria. The incidence of perioperative overall complications and death was pooled. Risk of bias was assessed using the revised Cochrane risk‐of‐bias tool. Results: Some 1384 studies were identified, of which four RCTs were included in the final analysis. These studies included 415 patients, of whom 213 (51·3 per cent) received standard treatment/placebo and 202 (48·7 per cent) had SDD. The incidence of anastomotic leakage (odds ratio (OR) 0·39, 95 per cent c.i. 0·19 to 0·80; P = 0·010) and pneumonia (OR 0·42, 0·23 to 0·78; P = 0·006) was reduced in patients receiving SDD. Rates of surgical‐site infection ( P = 0·750) and mortality ( P = 0·130) were not affected by SDD. Conclusion: SDD seems to be associated with reduction of anastomotic leakage and pneumonia following upper gastrointestinal resection, without affecting postoperative mortality. Abstract : This meta‐analysis investigated the influence of selective decontamination of the digestive tract (SDD) on outcomes after upper gastrointestinal surgery. SDD led to a reduction in anastomotic leakage (odds ratio (OR) 0·39, 95 per cent c.i. 0·19 to 0·80; P = 0·010) and pneumonia (OR 0·42, 0·23 to 0·78; P = 0·006). Further RCTs on SDD in upper gastrointestinal surgery are needed. Suggestion of better outcomes but not much evidence Abstract : Antecedentes: Las complicaciones infecciosas son frecuentes tras la cirugía gastrointestinal. La descontaminación selectiva del tracto digestivo ( Selective Decontamination of the Digestive tract, SDD) podría reducir su incidencia. Mientras que la SDD es ampliamente utilizada en las resecciones colorrectales, su papel en las resecciones del tracto gastrointestinal superior está menos definido. El objetivo de este estudio fue investigar el impacto de la SDD en el resultado postoperatorio en cirugía del tracto gastrointestinal superior. Métodos: Se incluyeron estudios que investigasen la SDD en cirugía del tracto gastrointestinal superior después de una búsqueda de bases de datos médicas (Pubmed, Ovid, Cochrane‐Library y Google/Scholar). Los resultados se analizaron de acuerdo con criterios predefinidos. Se agrupó la incidencia de complicaciones perioperatorias globales y mortalidad. El riesgo de sesgo se analizó utilizando la herramienta de la colaboración Cochrane revisada para la evaluación del riesgo de sesgo. Resultados: Se identificaron 1.380 estudios, de los cuales cuatro ensayos controlados aleatorizados fueron incluidos en el análisis final. Estos estudios incluían a 415 pacientes de los cuales 213 (51, 3%) recibieron tratamiento estándar/placebo y 202 (48, 7%) recibieron SDD. La incidencia de fugas anastomóticas (razón de oportunidades, odds ratio, OR: 0, 39 (0, 19–0, 80); P = 0, 010)) y neumonía (OR: 0, 42 (0, 23–0, 78); P = 0, 006)) se redujo en pacientes que recibieron SDD. Infecciones del sitio quirúrgico ( P = 0, 750) y la mortalidad ( P = 0, 130) no se relacionaron con la SDD. Conclusión: SDD parece asociarse con reducción de fuga anastomótica y neumonía tras resecciones del tracto gastrointestinal superior, sin afectar a la mortalidad postoperatoria.